Old holm oak coppices... new sylvopastoral practices - Bellon, S.; Guerin, G. (Plant Ecology, 1992)
In the south of France, holm oak (Quercus ilex L.) woodlands, particularly coppices, are currently used by livestock farmers. For this vegetation, a grazing allowance is available, based on the relationship between various layers. As far as livestock is concerned, such woodlands can be utilized for many purposes, e.g. stock feeding during critical periods and to provide flexibility to the pasture grazing se- quence. Furthermore, the related grazing intake patterns determine the level of holm oak utilization. Practices integrating both wood and livestock production provide a new perspective to the management of these woodlands in that the presence of livestock promotes specific operations which can lead to more diversified forestry. The renewal of both wood and pastoral resources depends on: (i) the initial level of integration of these two activities and (ii) subsequent technical operations. In the present paper a mid- term management scenario is developed which describes the likely development of woodlands with multiple use and periodic thinning.
Keywords: grazing allowance; resource management; sylvopastoral; thinning; Vegetation dynamics